2014
DOI: 10.2310/jim.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Obstructive Sleep Apnea: Clinical and Pathogenic Interactions

Abstract: Asthma and obstructive sleep apnea (OSA) are among the most prevalent chronic human diseases of the 21st century. They share several risk and aggravating factors such as obesity, smoking, gastroesophageal reflux, sinonasal disease or upper airway involvement, systemic inflammation, etc. Although the association between OSA and chronic obstructive pulmonary disease or "overlap syndrome" is better known and characterized, the association of asthma and OSA or "alternative overlap syndrome" is less clearly defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 146 publications
(201 reference statements)
0
21
0
2
Order By: Relevance
“…En el Community Health Respiratory Survey en el Reino Unido, se encontró que personas con asma de todas las edades y pesos roncaban con mayor frecuencia que los controles (29% vs. 9%). Así mismo, en los europeos, el autorreporte de ronquido habitual y apnea fue significativamente más frecuente en personas con asma comparados con los controles sin asma (14% vs. 9% y 3% vs. 1%, respectivamente), independientemente de su edad, peso corporal, sexo o tabaquismo (4).…”
Section: Riesgo De Sahos En Pacientes Asmáticosunclassified
See 1 more Smart Citation
“…En el Community Health Respiratory Survey en el Reino Unido, se encontró que personas con asma de todas las edades y pesos roncaban con mayor frecuencia que los controles (29% vs. 9%). Así mismo, en los europeos, el autorreporte de ronquido habitual y apnea fue significativamente más frecuente en personas con asma comparados con los controles sin asma (14% vs. 9% y 3% vs. 1%, respectivamente), independientemente de su edad, peso corporal, sexo o tabaquismo (4).…”
Section: Riesgo De Sahos En Pacientes Asmáticosunclassified
“…A pesar de que los fenotipos asma-obesidad y endotipos han sido descritos recientemente, sería interesante estudiar de manera sistemática la contribución de los trastornos respiratorios del sueño a todos ellos (4).…”
Section: Efectos Indirectosunclassified
“…The nocturnal upper airway stenosis and nocturnal hypoxia of OSAS have the potential to aggravate BA symptoms directly. In addition, TNF-a, interleukin-6, vascular endothelial growth factor, leptin, and other inflammatory mediators and adipokines produced during OSAS are believed to induce airway changes and sensitization, indirectly aggravating BA and making it intractable to treatment (2,4,5). Several epidemiologic studies have shown that BA patients are more likely than the public as a whole to have OSAS (6)(7)(8), thus suggesting an interaction between BA and OSAS.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiologic studies have shown that BA patients are more likely than the public as a whole to have OSAS (6)(7)(8), thus suggesting an interaction between BA and OSAS. In OSAS patients who develop BA, the lower airway stenosis due to BA increases the treatment intractability of OSAS, and BA-associated allergic rhinitis and steroid treatment may further exacerbate OSAS (2,4). Other studies, however, have failed to identify a direct interaction between OSAS and BA (9), and a clear consensus regarding the effects of OSAS and BA on each other has yet to be reached.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is considered an inflammatory disease of the airway that responds poorly to current therapies and affects more than 300 million individuals worldwide [1] . Severe persistent asthma can result in structural changes in the airway, such as thickening of the basement membrane, airway smooth muscle (ASM) hyperplasia and/or hypertrophy, changes in the extracellular matrix (ECM) composition and an increase in the number of blood vessels, which are collectively referred to as airway remodeling [2] [5] .…”
Section: Introductionmentioning
confidence: 99%